Analysis Of Environmental Health Impacts And Socio-Economic Impacts On The Rice Milling Industry - Safiu, Darwin; Setiono, Andik; Arif Atul Mahmuda Dullah; Alimin Alwi (Cita konsultindo, 2025)
This study aims to analyze the environmental health and socioeconomic impacts of the traditional rice milling industry in Tasikmalaya, focusing on potential hazards such as dust, noise, vibration, and hot working conditions that affect the health of workers and the surrounding community. The research method used was qualitative descriptive through field observations, interviews, and documentation of key informants and supporters, both from among workers and local residents. The results show that the highest dust concentrations are found around the milling and polishing machines, which have the potential to cause respiratory disorders. The continuous noise from the Fuso machines exceeds safe limits and threatens hearing function, while machine vibrations affect environmental comfort and building stability. Hot working conditions with poor ventilation cause discomfort and the risk of dehydration for workers. From a socioeconomic perspective, the rice milling industry makes an important contribution by creating jobs, increasing farmers' incomes, and strengthening the economic resilience of the community. However, there have also been changes in social structure and interaction patterns that tend to be more individualistic. This study concludes that risk control through dust management, noise reduction, and ventilation improvements is necessary to protect worker health and ensure the environmental and social sustainability of the rice milling industry.